Lixiviation as a tool for radionuclide fractionation in holm oak leaves - Tent, J.; Rauret, G. (JOURNAL OF RADIOANALYTICAL AND NUCLEAR CHEMISTRY-ARTICLES, 1996)
A sequential extraction scheme, using distilled water and chloroform : hexane(1:2) was applied in a study of radionuclide retention by helm oak leaves. To perform this study, holm oak leaves were contaminated by dry deposition using a thermogenerated radioactive aerosol containing Cs-134, Sr-85 and Ag-110m. The experimental parameters tested were: type and lime of shaking, number of successive extractions in each step, and the volume of extractans. From the results obtained, two schemes which give complementary information about radionuclide retention are proposed. The first scheme, using a single water extraction with mechanical shaking, allows us to define two fractions: the fraction removed by water, which is related to total radionuclide retention on leaf surfaces, and the residual fraction, which is associated with radionuclides incorporated into the leaves. The second scheme is based on a two-step extraction with manual shaking using water and chloroform :hexane, and permits us to distinguish among three fractions:the fraction removed by water(which is related to the radionuclide fraction easily leached by rain), the fraction removed by organic solvent (which is associated with the radionuclide fraction strongly retained on leaf surface), and the residual fraction, which may represent the absorbed radionuclide content. Since our objective was to study the retention of Cs-134, Sr-85 and Ag-110m, simultaneously, the experimental conditions chosen were a compromise of individual suitable conditions for each radionuclide.
APSAPSThe following values have no corresponding Zotero field: pub-location: PO BOX 245, H-1519 BUDAPEST, HUNGARY publisher: AKADEMIAI KIADO
Keywords: Holm oak; radionuclide

Deposition on holm oak leaf surfaces of accidentally released radionuclides - Rauret, G.; Llauradó, M.; Tent, J.; Rigol, A.; Alegre, L. H.; Utrillas, M. J. (Science of The Total Environment, 1994)
The retention of aerosols by canopies of holm oak trees in a typical Mediterranean forest is studied. Firstly, dry deposition is measured both under and outside the canopy during several months. No clear differences are observed either in the amount or in the chemical composition of the particles collected under and outside the canopy. Secondly, the leaf morphology and anatomy as well as the aerosol deposited onto the leaf surfaces are studied by scanning electron microscopy. Cuticle thickness is measured and differences are observed between young and old leaves. The distribution of aerosol particles over leaf surface is also established. Finally, the possible incorporation into leaves of a radioactive aerosol released in an accidental situation is studied, by means of a sequential extraction procedure using water and an organic solvent. From the results it can be deduced that neither the abiotic layer nor the cuticle play any important role in the retention of caesium. The studied radionuclides are mainly found in particulate form, soluble in water, or incorporated into leaves.
Keywords: Cuticle thickness; Holm oak; Leaf surface; Radionuclide deposition; Radionuclide incorporation; Sequential extraction